FTIR-based Fingerprinting and Chemometrics for Rapid Investigation of Antioxidant Activity from Syzygium polyanthum Extracts - Eti Rohaeti; Fadila Karunina; Mohamad Rafi (Universitas Gadjah Mada, 2021)
Syzygium polyanthum, known as salam in Indonesia, which is rich in phenolics compounds with high antioxidant activity. In this study, we performed the determination of total phenolics and characterization of the antioxidant activity of S. polyanthum leaves extracts using the FTIR-based fingerprinting technique. The extracts of S. polyanthum in water, ethanol, and ethanol-water (30, 50, and 70%) were measured for their antioxidant activity, total phenolics, and FTIR spectra. The antioxidant activity of S. polyanthum extract with different solvent extraction showed the highest antioxidant activity and total phenolic content is 70% and 50% ethanolic extract, respectively. The FTIR spectrum of each extract showed identical FTIR spectra patterns. According to their different solvent extraction, S. polyanthum extract could be grouped based on FTIR spectra using principal component analysis. Correlation between the functional group in the FTIR spectra with IC50 from S. polyanthum extract was analyzed using partial least square (PLS). The PLS analysis results showed that O–H, C–H sp3, C=O, C=C, C-O, and C–H aromatic are the main functional groups contributed to the antioxidant activity of S. polyanthum extract. FTIR-based fingerprinting combined with chemometrics could be used to classify different extracts of S. polyanthum and predicted functional groups having a significant contribution to antioxidant activity.